A Primary Mediastinal Large B-Cell Lymphoma Patient With COVID-19 Infection After Intensive Immunochemotherapy: A Case Report - Li, Qiuhui; Zhu, Fang; Xiao, Yin; Liu, Tao; Liu, Xinxiu; Wu, Gang; Zhang, Liling (Frontiers in Oncology, 2020)
Background: The outbreak of coronavirus disease 2019 (COVID-19) had become a global public health event. Lymphoma patients need to be distinguished from the general population because of their deficient immune status and intensive anti-tumor treatment. The impacts of cancer subtypes and treatment on COVID-19 infection are unclear. Case Presentation: We here report the case of a primary mediastinal large B-cell lymphoma patient who was infected with COVID-19 after intensive immunochemotherapy (DA-EPOCH-R). The patient developed a neutropenic fever during chemotherapy, and fever was persistent, although antibiotics were used. Initial chest CT was negative, and the patient received a throat swab test since the second CT showed evidence of pneumonia. With treatment with Arbidol Hydrochloride and LianHuaQingWen capsule, his COVID-19 was cured. Conclusions: To the best of our knowledge, this is the first report focusing on COVID-19 infection in a lymphoma patient undergoing intensive immunochemotherapy. For those patients being treated with immunochemotherapy in epidemic areas, a reduced dose intensity of intensive chemotherapy should be considered, and the effect of immunotherapies such as rituximab on COVID-19 infection should be considered. The impacts of anti-cancer treatment on COVID-19 infection need to be explored further.